B cell immune profiles in dysbiotic vermiform appendixes of pancreatic cancer patients - Vietsch, Eveline E.; Latifi, Diba; Verheij, Maaike; van der Oost, Elise W.A.; de Wilde, Roeland F.; Haen, Roel; van den Boom, Anne Loes; Koerkamp, Bas Groot; Doornebosch, Pascal G.; van Verschuer, Victorien M.T.; Ooms, Ariadne H.A.G.; Mohammad, Farzana; et al. (Frontiers in Immunology, 2023)
Pancreatic ductal adenocarcinoma (PDAC) remains one of the deadliest solid tumors and is resistant to immunotherapy. B cells play an essential role in PDAC progression and immune responses, both locally and systemically. Moreover, increasing evidence suggests that microbial compositions inside the tumor, as well as in the oral cavity and the gut, are important factors in shaping the PDAC immune landscape. However, the gut associated lymphoid tissue (GALT) has not previously been explored in PDAC patients. In this study we analyzed healthy vermiform appendix (VA) from 20 patients with PDAC and 32 patients with colon diseases by gene expression immune profiling, flow cytometry analysis and microbiome sequencing. We show that the VA GALT of PDAC patients exhibits markers of increased inflammation and cytotoxic cell activity. In contrast, B cell function is decreased in PDAC VA GALT based on gene expression profiling, B cells express significantly less MHC class II surface receptors, whereas plasma cells are expressing immune checkpoint molecule HLA-G. Additionally, the vermiform appendix microbiome of PDAC patients is enriched with Klebsiella pneumoniae, Bifidobacterium animalis and Adlercreutzia equolifaciens, while certain commensals are depleted. Our 2 findings may suggest impaired B cell function within the GALT of PDAC patients, which could potentially be linked to microbial dysbiosis. Additional investigations are imperative to validate our observations and explore these potential targets of future therapies.